2006
DOI: 10.1126/science.1123604
|View full text |Cite
|
Sign up to set email alerts
|

Rice Domestication by Reducing Shattering

Abstract: Crop domestication frequently began with the selection of plants that did not naturally shed ripe fruits or seeds. The reduction in grain shattering that led to cereal domestication involved genetic loci of large effect. The molecular basis of this key domestication transition, however, remains unknown. Here we show that human selection of an amino acid substitution in the predicted DNA binding domain encoded by a gene of previously unknown function was primarily responsible for the reduction of grain shatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
713
1
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 787 publications
(778 citation statements)
references
References 16 publications
30
713
1
9
Order By: Relevance
“…Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 . However, the well-characterized domestication genes in rice were found to be fixed in both subspecies with the same alleles, thus supporting a single domestication origin [6][7][8][9]16 . Recently, a demographic analysis of single-nucleotide polymorphisms (SNPs) detected from 630 gene fragments suggested a single domestication origin of rice 17 .…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 . However, the well-characterized domestication genes in rice were found to be fixed in both subspecies with the same alleles, thus supporting a single domestication origin [6][7][8][9]16 . Recently, a demographic analysis of single-nucleotide polymorphisms (SNPs) detected from 630 gene fragments suggested a single domestication origin of rice 17 .…”
mentioning
confidence: 83%
“…We noticed that many loci with strong signals of selection were nearly identical in both indica and japonica where F ST between indica and japonica was extremely low, indicating that introduction of traits during domestication has in many cases involved introgression events. We noted that most well-characterized domestication genes, including Bh4 (hull colour 9 ), PROG1 (tiller angle 7,8 ), sh4 (seed shattering 5,6 ), qSW5 (grain width 35 ) and OsC1 (leaf sheath colour and apiculus colour 32 ), were among the 55 loci detected in the full population (Fig. 3).…”
Section: Screens and Annotation Of Domestication Locimentioning
confidence: 95%
See 1 more Smart Citation
“…In this case three different domestication trait mutants, waxy (wx), shattering (qsh1) and seed width (qsw5) appear to come from three different geographic regions, giving rise to a mosaic very much like that predicted in Fig 3b. The rice studies also indicate that there are multiple shattering mutants, sh4 (Li et al, 2006) and qsh1 (Konishi et al, 2006). In this case sh4 is present in all tested domesticated rice varieties (Lin et al, 2007), while qsh1 is restricted to the Japanese area where it presumably arose, and occurred after the wx and qsw5 mutants had arisen in different areas and been combined, possibly in the Thailand area (Shomura et al, 2008).…”
Section: The Chronology Of Trait Fixationmentioning
confidence: 99%
“…Recent functional genomic studies have helped to excavate a number of domestication genes [26][27][28][29]. For example, sh4 and qSH1 are essential for effective field harvest because of their ability to reduce grain shattering [29,30]. In addition, grain or fruit size was important in the evolution of wild species because of the continuous selection for large ones during early domestication.…”
Section: Introductionmentioning
confidence: 99%